INCREASING ONLINE SHOP APPLICATIONS DURING THE COVID-19 PANDEMIC - Nirwana, Devi (LPPM Universitas Bina Bangsa, 2024)
During the current Covid-19 pandemic, people have reduced their activities outside the house, including shopping, to meet their needs. Using online stores for shopping has become an alternative solution, but the benefits, drawbacks and what is available in online store applications need to be researched so as not to cause harm to consumers. This research aims to find out and analyze the benefits of online shop applications. It is hoped that the research results will provide benefits for consumers in using online shops and for online shop owners they can become a reference for improving services. This research method is descriptive analysis of data obtained through a questionnaire with questions related to the benefits of online stores in the e-commerce marketplace. Factors in terms of delivery of goods and the quality of the products received by consumers are of concern in this research as well as suggestions for problem solving that can be carried out by online shop managers. The conclusion obtained is, to be able to help consumers shop online during the pandemic, suggestions for choosing an online shop with good delivery services and assessing the quality of goods are needed by consumers.